Bedside testing for myasthenia gravis: the ice-test. (19th November 2010) - Browning, J; Wallace, M; Chana, J; Booth, J
Abstract : A 67-year-old man presented to the acute medical take with a history of droopy eyelids and difficulty swallowing. A diagnosis of myasthenia gravis was suspected from the clinical history. The patient's symptoms were progressive, raising concerns of aspiration pneumonia or respiratory compromise if untreated. Definitive diagnosis of myasthenia gravis relies upon a combination of serological and electrophysiological investigations, the results of which are not immediately available in an acute situation. Bedside tests are therefore of practical clinical importance to enable prompt and effective initiation of treatment, particularly where critical symptoms are present. The ice-test is a straightforward and non-invasive investigation with a high sensitivity for myasthenia gravis and is a useful alternative to edrophonium testing. It is especially helpful in patients with cardiac and respiratory co-morbidities for whom acetylcholinesterase inhibitors are contraindicated. We describe a case where this simple bedside test successfully expedited the correct treatment and improved patient care.